Features of Hemodynamics in Elderly Patients Undergoing CABG Surgery at the Stage of Induction Anesthesia - Vitovskyi, Andrii R. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Due to the global trend of the population ageing, an important task of modern medicine is to improve the provision of medical care for elderly patients. These people have reduced compensatory reserves of the body and numerous chronic pathologies, necessitating a more meticulous approach to anesthesia induction and maintenance by anesthesiologists. According to the authors, the use of propofol and fentanyl leads to decreased myocardial contractility and reduction in overall peripheral vascular resistance. However, the resulting decrease in perfusion pressure in vital organs and tissues, as a consequence of the aforementioned effects, is unacceptable in elderly patients with coronary heart disease (CHD). The aim. To analyze changes in hemodynamics in elderly patients undergoing coronary artery bypass grafting (CABG) during the induction of anesthesia. Materials and methods. A prospective study was conducted which included the results of examination of 20 patients with CHD over 60 years old who underwent CABG without the use of cardiopulmonary bypass at the National Amosov Institute of Cardiovascular Surgery (Kyiv, Ukraine). The mean age of the patients was 67.5±6.8 years. There were 16 (80%) men and 4 (20%) women. Typical manifestations of heart failure were noted (there were 1 [5%], 10 [50%] and 9 [45%] NYHA functional class I, II and III patients, respectively). Also, the patients were classified according to the Canadian classification of angina: 1 (5%), 9 (45%) and 10 (50%) patients fell within class I, II and III, respectively. Stage 2-3 hypertension was reported in 18 patients (90%). For induction of anesthesia, the following medications were used: propofol 1.5 mg/kg, fentanyl 2.0 μg/kg, and rocuronium bromide 0.1 mg/kg. Anesthesia maintenance included: propofol 4 mg/kg/hour, fentanyl 2.0 μg/kg/hour. Hemodynamic parameters saturation indices (SpO2), and transthoracic echocardiography parameters were recorded at the following stages: 1) upon the patient’s arrival in the operating room; 2) prior to tracheal intubation; 3) immediately after tracheal intubation; 4) 25 minutes after intubation. Results. Upon arrival in the operating room, the hemodynamic parameters reflected stable general condition of the examined patients. After administration of induction agents according to the study design, it was recorded that mean blood pressure (BP) was 72.7±4.76% (p<0.001), heart rate was 89.8±5.95% (p=0.0004), cardiac index was 81.47±6.6% (p<0.001), and systemic vascular resistance index (SVRI) was 89.9±7.02% of the baseline values (p=0.063). After intubation, an increase in most hemodynamic indicators was observed, although only mean BP, which constituted 86.7±8.8% of the baseline data (p<0.001), and SVRI (89.8±11.04% of the baseline data, p=0.0315), significantly differed from the baseline values. Within 25 minutes after the intubation, the parameters decreased again: with mean BP 74.9±7.9% (p<0.001), heart rate 91.3±9.5% (p=0.008), cardiac index 79.6±10.1% (p<0.001), and SVRI 91.1±9.34% (p=0.062) of the baseline values. Conclusions. The main changes in hemodynamics were reported during induction of anesthesia, where a significant decrease in most indicators compared to the baseline state was recorded. After intubation, the parameters slightly increased but did not return to the baseline values. During further anesthesia maintenance, a significant decrease in most indicators relative to the baseline data were observed. The instability of hemodynamic parameters during the induction stage of anesthesia in elderly patients with CHD can be an obstacle to the normal course of the perioperative period, necessitating the search for methods to stabilize them.